Two-Step Pyrolysis Process for Producing High Quality Bio-Oils - Garrido-Lazo, R (American Chemical Society, 2015)
A newly developed two-step pyrolysis process for the fractionation of lignocellulosic biomass components into sugar-rich and lignin-derived rich bio-oils by using pinewood as the feedstock has been studied. In the first step, biomass is pyrolyzed between 300 and 350 °C decomposing cellulose and hemicellulose fibers to produce bio-oil having significantly higher selectivities toward sugars and lower selectivities toward low molecular weight oxygenated compounds, such as organic acids, aldehydes, and ketones than those of bio-oil produced from the conventional one-step pyrolysis at 500 °C. In the second step, the lignin-rich biomass remaining was pyrolyzed in the presence of HZSM-5 catalyst to produce aromatic-rich bio-oil with low selectivity toward oxygenated compounds. Comparison with the conventional one-step 500 °C catalytic pyrolysis showed the advantage of biomass "heat pretreatment" in the first-step pyrolysis, which promoted the decomposition of lignin to monomeric phenolic compounds which were more easily converted to aromatics. Application of catalytic pyrolysis to both steps produced two bio-oil fractions, combined, having significantly higher selectivity toward aromatics and lower selectivity toward oxygenated compounds. Over the conventional one-step pyrolysis, by decomposing biomass components separately at different pyrolysis temperature levels, the developed two-step pyrolysis process allows more flexibility for producing bio-oils with specific composition of chemical moieties that meet the requirements for their desired end uses. © 2015 American Chemical Society.